Phenolic Compound Ethyl 3,4-Dihydroxybenzoate Retards Drug Efflux and Potentiates Antibiotic Activity - Lu, Wen-Jung; Huang, Yan-Jyun; Lin, Hsuan-Ju; Chang, Chun-Ju; Hsu, Pang-Hung; Ooi, Gui-Xia; Huang, Mei-Ying; Lin, Hong-Ting Victor (Antibiotics (Basel), 2022)
The World Health Organization indicated that antibiotic resistance is one of the greatest threats to health, food security, and development in the world. Drug resistance efflux pumps are essential for antibiotic resistance in bacteria. Here, we evaluated the plant phenolic compound ethyl 3,4-dihydroxybenzoate (EDHB) for its efflux pump inhibitory (EPI) activity against drug-resistant Escherichia coli. The half-maximal inhibitory concentration, modulation assays, and time-kill studies indicated that EDHB has limited antibacterial activity but can potentiate the activity of antibiotics for drug-resistant E. coli. Dye accumulation/efflux and MALDI-TOF studies showed that EDHB not only significantly increases dye accumulation and reduces dye efflux but also increases the extracellular amount of antibiotics in the drug-resistant E. coli, indicating its interference with substrate translocation via a bacterial efflux pump. Molecular docking analysis using AutoDock Vina indicated that EDHB putatively posed within the distal binding pocket of AcrB and in close interaction with the residues by H-bonds and hydrophobic contacts. Additionally, EDHB showed an elevated postantibiotic effect on drug-resistant E. coli. Our toxicity assays showed that EDHB did not change the bacterial membrane permeability and exhibited mild human cell toxicity. In summary, these findings indicate that EDHB could serve as a potential EPI for drug-resistant E. coli.